(untitled) (Vietnam Journal of Community Medicine, 2025)
Objectives: To assess knowledge and attitudes towards sexual and reproductive health among adolescents and adults in Son La province. Objects and methods: A cross-sectional study was conducted with 1012 participants, including 382 students and 630 adults in communes/wards of Son La province. Results: 81.7% of adolescents knew about male condoms, while adults had a higher awareness of contraceptive rings and contraceptive injections. Notably, 66% of adolescents reported feeling ashamed when seeking contraceptives, while the rate was lower among adults, at 58.1%. In addition, only 41.6% of adolescents understood how to use emergency contraceptive pills compared to 69.5% of adults. Regarding attitude towards sexual reproductive health, 66.2% of adolescents said that premarital sex was unacceptable, compared to 57.6% of adults. Conclusion: There is a need to raise awareness and education about sexual and reproductive health for both groups, especially focusing on providing knowledge about contraceptive methods and safe sex skills for adolescents. Reproductive health education programs should incorporate practical and accessible methods to enhance community confidence and understanding of reproductive health.